The Effect of Learning Tabletop Disaster Exercise (TDE) to Improve Knowledge among Nursing Students for Disaster Emergency Response - Mukhamad Fathoni; Yuyun Yueniwati Prabowowati Wadjib; Widya Addiarto (Research Journal of Life Science, 2019)
Today, the high incidence of disasters requires nurses to increase their role as disaster nursing in emergency response. This is in accordance with standards of the international council of nursing (ICN) that the nurse as a front line in providing treatment of disaster victims. One of the way to do in these situations is to improve the early preparedness in nursing students through disaster education, so that this plan needs a new method for effective and innovative disaster learning. One of the recommendation learning method is simulation with Tabletop Disaster Exercise (TDE). The purpose of this study was to analyze the effect of TDE learning for undergraduate nursing student’s knowledge in providing the management of victims in disaster response simulations. This study uses quasy experimental with pre-post test and control group design. The samples are 36 respondents were divided into two groups there are treatment and control groups so that each consisting of 18 respondents. The treatment group were given a TDE simulation, while the control group was given standard simulation and module. The results using paired t-test significantly showed that the differences value of knowledge before and after intervention with difference Pre-test 18 respondents mean 23.89±9.00 and Post test 18 respondents mean 81.67±8.04 Difference  Mean (CI 95%) = 57.78 (53.85-61.71) in each group indicated by the value (p = 0.000). The Effect Simulation Standards Knowledge Nursing Students with difference Pre test 18 respondents mean 26.39±9.04 and Post test 18  respondents mean 70.28±10.07 Difference  Mean (CI 95%) = 43.89 (38.59-49.18). The results from unpaired t-test to identify the difference of knowledge between the two groups after intervention has a significance value (p = 0.000). This means that there is significant difference of knowledge between TDE simulation and simulation.